Peningkatan Pembelajaran Permainan Bolavoli Kelas VIII SMPN 1 Suralaga Menggunakan Articulate Storyline - Azhari, Haeruddin; Abdullah, Catur Prima Eka Putra; Prasetyo, Muhammad Teguh; Hamzah, Hamzah (Jurnal Porkes, 2024)
The purpose of this research is to develop articulate storyline-based interactive media products in volleyball games for SMPN 1 Suralaga students which will be used as a learning tool by a teacher in improving the cognitive abilities of students. The development of learning media as a technology-based learning tool that is in accordance with the times in stimulating cognitive, learning motivation and quality in learning so that learning outcomes are getting better. This product development uses the ADDIE model which consists of need assessment, design, development, implementation, evaluation. The population in this study were all students of SMPN 1 Suralaga and the sample in this study were 30 students. The data collection technique in this research and development uses a questionnaire technique with answer choices using a Likert scale of 1 to 4. The results of the 93% (very valid) bolavoli learning validation test, 90% (very valid) bolavoli material expert validation, 96% (very valid) learning media expert validation, 93% (very feasible) small group trial, and 85% (very interested) average attractiveness test. The conclusion of research and development of interactive learning media based on articulate storyline in volleyball games can provide interest in learning for students of SMPN 1 Suralaga.